2022
DOI: 10.1103/physrevlett.128.167002
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Superconductivity from Nonlocal Coulomb Repulsion in an Atomic Sn Layer Deposited onto a Si(111) Substrate

Abstract: Atomic layers deposited on semiconductor substrates introduce a platform for the realization of the extended electronic Hubbard model, where the consideration of electronic repulsion beyond the on-site term is paramount. Recently, the onset of superconductivity at 4.7 K has been reported in the hole-doped triangular lattice of tin atoms on a silicon substrate. Through renormalization group methods designed for weak and intermediate coupling, we investigate the nature of the superconducting instability in hole-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 67 publications
(98 reference statements)
2
22
0
Order By: Relevance
“…In addition, due to the lack of spatial inversion symmetry, an antisymmetric Rashba spin-orbit coupling (SOC) is induced [22]. However, previous local density approximation (LDA) calculations have revealed that this effect is very small and barely affects the band structure of the system [15]. Thus we will ignore Rashba SOC.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, due to the lack of spatial inversion symmetry, an antisymmetric Rashba spin-orbit coupling (SOC) is induced [22]. However, previous local density approximation (LDA) calculations have revealed that this effect is very small and barely affects the band structure of the system [15]. Thus we will ignore Rashba SOC.…”
Section: Methodsmentioning
confidence: 99%
“…The non-interacting energy dispersion is then given by where the first neighbor hopping is set to t 1 = −52.7 meV. Relative to t 1 , the other hopping parameters are given by t 2 /t 1 = −0.389, t 3 /t 1 = 0.144, and t 4 /t 1 = −0.027 [14,15]. Besides, µ is the chemical potential, which varies with doping.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations